2021
DOI: 10.1108/jm2-09-2020-0229
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of CMMI level of manufacturing industry using fuzzy logic approach: a case study

Abstract: Purpose The purpose of this study is to develop a CMMI model for the manufacturing industry and to find an appropriate method to assess the CMMI level. The CMMI level indicates how well the processes are planned, performed, measured and controlled, thus revealing the performance level of an organization. Design/methodology/approach Among the various process areas of CMMI, “organizational process focus” (OPF) is selected for the study. The CMMI model for the process area OPF is designed based on the CMMI enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…As a result, these Process areas are relevant to and valuable in the manufacturing industry. For instance, in the case studies by Raghuram et al (2020) and Thomas et al (2021), the CMMI approaches were employed in the process appraisal of manufacturing industries. Among the different process areas of CMMI, OPF is selected for the investigation considering the process enhancement for the growth of digitalisation in the manufacturing sector.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, these Process areas are relevant to and valuable in the manufacturing industry. For instance, in the case studies by Raghuram et al (2020) and Thomas et al (2021), the CMMI approaches were employed in the process appraisal of manufacturing industries. Among the different process areas of CMMI, OPF is selected for the investigation considering the process enhancement for the growth of digitalisation in the manufacturing sector.…”
Section: Methodsmentioning
confidence: 99%
“…The extensive literature review revealed the requisite facilities, resources and managerial skills required in the process area OPF pertaining to digital manufacturing. The multi-level CMMI model for the process area OPF was adopted from the literature (Thomas et al, 2021) and modified to assess the digital manufacturing maturity of an organisation. The CMMI multilevel model comprises three enablers, nine criteria and 57 attributes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expert questionnaire sheet for gathering expert opinion has been shown in Appendix. To handle imprecise data in multi-criteria decision making, Pythagorean and Intuitionistic fuzzy sets were used frequently; however, it is difficult for them to explain the information which is ambiguous and complex (Thomas et al, 2021). Such complex information can be easily expressed well using triangular fuzzy numbers.…”
Section: Methodsmentioning
confidence: 99%